Degradation of Organophosphorus Pesticides in Pear by Ozonation - Fu, Ying; Li, Yu; Ye, Fei (Asian Journal of Chemistry, 2014)
The present study investigated the degradation of two organophosphorus pesticides i.e., malathion and dimethoate, in pear by ozonation in order to establish the effect of operational parameters. Four degradation methods were conducted and ozonation was the most effective way with its advantages of cleanness, convenience and facility. The optimized ozonation conditions of degradation of malathion and dimethoate in pear were as following: the degradation mode was bubbling ozone in water and the degradation time was 0.5 h. The two organophosphorus pesticides could be degraded over 60 % in 0.5 h by bubbling ozone. There was no effect on fruit quality after treatment with ozone.